ANALYSIS OF DOCUMENTS RELATED TO THE HISTORY OF THE NATIONAL UNIVERSITY OF UZBEKISTAN IN THE CENTRAL STATE ARCHIVE OF TASHKENT CITY - Yusupova Dildora,Musoyev Umirzoq (International Journal of Literature and Language Studies, 2026)
This article presents a formal source-based analysis of archival documents relating to the history of the National University of Uzbekistan, preserved in Fund R-38 of the Central State Archive of Tashkent City. The study focuses on Inventory No. 3, a collection of permanent-storage records covering 1949-1988 and reflecting the institutional, educational, scientific and administrative activity of Tashkent State University during the Soviet period. The article examines the formation of the fund, the typological structure of its documents, the evidence of organizational transformations and the value of these records for reconstructing the history of higher education in Uzbekistan. Special attention is given to rectorial orders, academic council minutes, annual plans and reports, faculty and department documentation, patent-office materials, postgraduate training records and personnel files. The analysis demonstrates that Fund R-38 is a complex historical source that reveals the mechanisms of academic governance, state educational policy, research specialization and the formation of intellectual elites. The article also notes the methodological limitations caused by missing and poorly preserved files and argues for urgent digitization, systematic description and wider scholarly use of the fund.